The Strategic Role of Work-Life Balance in Female Employee Loyalty at the Palu City Building Union - Ririn Safitri; Awaluddin; Abdul Rahman (Universitas Muhammadiyah Palu, 2026)
This study aims to determine and describe the work-life balance conditions experienced by female employees, identify factors that influence work-life balance, and analyze the strategic role of work-life balance in shaping female employee loyalty at Union Bangunan Kota Palu. This study uses a qualitative approach with a descriptive research type. Research informants consisted of female employees in the service and administration departments selected using purposive sampling techniques. Data collection techniques were carried out through in-depth interviews, observation, and documentation. Data analysis used the Miles and Huberman model which includes data reduction, data presentation, and conclusion drawing. The results show that the work-life balance conditions of female employees at Union Bangunan Kota Palu are influenced by organizational support, flexible work schedules, family support, and a harmonious work environment. The main inhibiting factors include busy working hours, physical fatigue, and high customer service demands. Work-life balance plays a strategic role in shaping female employee loyalty by creating a sense of comfort, job satisfaction, responsibility, and emotional attachment to the organization. Female employees who feel organizational support tend to show higher commitment and desire to stay despite facing considerable work pressure.